Interaction and language development through group work: Indonesian EFL learners’ perspectives at an Australian university - Siti Rahimah Yusra; Rizaldy Hanifa; Andri Wardana; Riki Muhamanda (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2026)
This study investigates how Indonesian EFL learners are supported by group work interactions during study abroad at an Australian university. The study employed a descriptive qualitative design, driven by the Interaction Hypothesis, the Output Hypothesis, and Sociocultural Theory. Data were collected from a questionnaire completed by 15 graduate students. The questionnaire consisted of 19 Likert items and three open-ended questions addressing performance, learning opportunities, and language comprehension. Open-ended responses were discussed qualitatively with little inference, while Likert-type results were summarized descriptively. Regular group work increased speaking opportunities, enhanced lexical acquisition through peer modeling and simple explanations, and encouraged metacognitive regulation, as well as boosting communicative confidence. However, perceived gains in complexity and accuracy were inconsistent, reflecting differing perspectives on corrective feedback, unequal psychological safety, and challenges arising from peer dominance and peer grouping. Maximum benefits may be obtained when roles equalize access to task scope, tasks require joint approval, feedback is delivered through self-respect-preserving scripts, brief planning–monitoring–evaluation checkpoints are inserted, and peer networks extend beyond nationality-based circles. This study explains how peer interactions are transformed by modified input, encouraged output, and mediated participation in a multilingual and multicultural higher education environment by centering lived experiences and identifying sociocultural moderators.